Pengaruh Online Customer Reviews, Social Media Marketing, Serta Keberagaman Produk Terhadap Brand Image Dan Brand Trust Di Dragon Diamond - Rifky Abdul Akbar; Rivera Pantro Sukma (LPPM Universitas Asa Indonesia, 2025)
This study aims to analyze the influence of online customer reviews, social media marketing, and product diversity on brand image and brand trust as variables in Dragon Diamond. This study uses a quantitative approach with an accidental sampling method through a questionnaire distributed to 200 respondents who have interacted with Dragon Diamond digitally. Data analysis was carried out using the Structural Equation Modeling (SEM) method with the help of SmartPLS 3.0 software. The results of the study indicate that online customer reviews do not have a significant effect on brand image, but have a significant effect on brand trust. Social media marketing does not have a significant effect on brand image or brand trust. Product diversity has a significant effect on brand image, but not on brand trust. In addition, brand image is not proven to have a significant effect on brand trust.